Cognitive Vulnerability to Depression in Canadian and Chinese Adolescents - Auerbach, Randy P. (Springer US, 2009)
The goal of the current study was to compare diathesis-stress and transactional models of cognitive vulnerability to depression in samples of Canadian (n = 118) and Chinese (n = 405) adolescents. We utilized a six-month multi-wave, longitudinal design in order to examine whether (a) perceived control moderated the association between the occurrence of dependent interpersonal stressors and subsequent increases in depressive symptoms (i.e., a diathesis-stress perspective) and (b) dependent interpersonal stressors mediated the association between perceived control and subsequent increases in depressive symptoms (i.e., a transactional perspective). Results from idiographic, time-lagged, hierarchical linear modeling analyses indicated that for Canadian adolescents both diathesis-stress and transactional models were significant predictors of depressive symptomology. When examining the diathesis-stress model, boys, but not girls, who reported lower perceived control, reported higher levels of depressive symptoms following the occurrence of dependent interpersonal stress. Gender differences, however, were not present in the transactional model. In contrast, transactional, but not diathesis-stress, models were significant in Chinese adolescents, and gender differences did not emerge. Overall, these results may reflect culturally-relevant differences in the etiology of depression in Canadian and Chinese adolescents.